Diseño e implementación de un sistema de control y monitoreo de temperatura ambiental y humedad relativa del suelo, para el mejoramiento de la calidad de un invernadero ubicado en la ciudad de Pujilí, periodo 2017. - Suntasig Guilcaso, Henry Vinicio (2018)
The control systems allow to manage, direct regulate another system to improve its production or decrease its likelihood of failure. This researched work presents the design of a control system based on the manipulation of the environmental variables of temperature and humidity about ground that exist inside of a greenhouse, applying sensors that constantly collect data of these variables, and according to the requirements they activate actuators that will allow to control the ventilation and humidity respectively. It has been done a bibliography review of different authors for determining the properties and characteristics of each element of the system (sensors, actuators, etc.) thanks so that, it could determine the relevant details for the start-up of all components. In addition, each used connection with each element is detailed during the automation process and the final graphical interface in which the farmer can look at the environmental conditions in which the greenhouse is located and the humidity of the ground in which are the crops. As a result, an adequate environment will be obtained inside the greenhouse which is adapted for the growth of the crops in an optimal way, the economic feasibility of the project is favorable because the implementation cost is recoverable in a reasonable periods of time.